International variation in dialysis discontinuation in patients with advanced kidney disease - Jassal, Sarbjit V.; Larkina, Maria; Jager, Kitty J.; Murtagh, Fliss E.M.; O’Hare, Ann M.; Hanafusa, Norio; Morgenstern, Hal; Port, Friedrich K.; McCullough, Keith; Pisoni, Ronald; Tentori, Francesca; Perlman, Rachel; et al. (CMAJ : Canadian Medical Association journal = journal de l'Association medicale canadienne, 2020)
BACKGROUND: Decisions about dialysis for advanced kidney disease are often strongly shaped by sociocultural and system-level factors rather than the priorities and values of individual patients. We examined international variation in the uptake of conservative approaches to the care of patients with advanced kidney disease, in particular discontinuation of dialysis. METHODS: We employed an observational cohort study design using data collected from patients maintained on long-term hemodialysis between 1996 and 2015 in facilities across 12 developed countries participating in the Dialysis Outcomes and Practice Patterns Study (DOPPS). The main outcome was discontinuation of dialysis therapy. We analyzed the association between several patient characteristics and time to dialysis discontinuation by country and phase of study entry. RESULTS: A total of 259 343 DOPPS patients contributed data to the study, of whom 48 519 (18.7%) died during the study period. Of the decedents, 5808 (12.0%) discontinued dialysis before death. Rates of discontinuation were higher within the first few months after initiation of dialysis, among older adults, among those with a greater number of comorbidities and among those living in an institution. After adjustment for age, sex, dialysis duration, diabetes and dialysis era, rates of discontinuation were highest in Canada, the United States and Australia/New Zealand (33.8, 31.4 and 21.5 per 1000/yr, respectively) and lowest in Japan and Italy (< 0.1 per 1000/yr). Crude discontinuation rates were highest in dialysis facilities that were more likely to offer comprehensive conservative renal care to older adults. INTERPRETATION: We found persistent international variation in average rates of dialysis discontinuation not explained by differences in patient case-mix. These differences may reflect physician-, facility- and society-level differences in clinical practice. There may be opportunities for international cross-collaboration to improve support for patients with end-stage renal disease who prefer a more conservative approach.
Keywords: Nephrology; Hematology & transfusion medicine